Fragmented implementation of maternal and child health home-based records in Vietnam: need for integration - Hirotsugu Aiga; Vinh Duc Nguyen; Cuong Dinh Nguyen; Tho Thi Thi Nguyen; Lien Thi Phuong Nguyen (Taylor & Francis Group, 2016)
Background: Home-based records (HBRs) are globally implemented as the effective tools that encourage pregnant women and mothers to timely and adequately utilise maternal and child health (MCH) services. While availability and utilisation of nationally representative HBRs have been assessed in several earlier studies, the reality of a number of HBRs subnationally implemented in a less coordinated manner has been neither reported nor analysed. Objectives: This study is aimed at estimating the prevalence of HBRs for MCH and the level of fragmentation of and overlapping between different HBRs for MCH in Vietnam. The study further attempts to identify health workers' and mothers' perceptions towards HBR operations and utilisations. Design: A self-administered questionnaire was sent to the provincial health departments of 28 selected provinces. A copy of each HBR available was collected from them. A total of 20 semi-structured interviews with health workers and mothers were conducted at rural communities in four of 28 selected provinces. Results: Whereas HBRs developed exclusively for maternal health and exclusively for child health were available in four provinces (14%) and in 28 provinces (100%), respectively, those for both maternal health and child health were available in nine provinces (32%). The mean number of HBRs in 28 provinces (=5.75) indicates over-availability of HBRs. All 119 minimum required items for recording found in three different HBRs under nationwide scale-up were also included in the Maternal and Child Health Handbook being piloted for nationwide scaling-up. Implementation of multiple HBRs is likely to confuse not only health workers by requiring them to record the same data on several HBRs but also mothers about which HBR they should refer to and rely on at home. Conclusions: To enable both health workers and pregnant women to focus on only one type of HBR, province-specific HBRs for maternal and/or child health need to be nationally standardised. Moreover, to ensure a continuum of maternal, newborn, and child health care, the HBRs currently fragmented into different MCH stages (i.e. pregnancy, delivery, child immunisation, child growth, and child development) should be integrated. Standardisation and integration of HBRs will help increase technical efficiency and financial sustainability of HBR operations.